A Review on Purification Methods of Bromelain from Pineapple Stems: Bromelain Purification Methods - Paroma Arefin; Md. Shehan Habib; Md. Saidul Arefin; Aishawarya Arefin (Biological Sciences - PJSIR, 2023)
Bromelain comprises a group of proteolytic enzymes attained from the tissue of pineapple, Ananas comosus, belonging to the Bromeliaceae plant family. Different studies indicated its antithrombotic, fibrinolytic, antimicrobial, anticancer and anti-inflammatory properties. Bromelain has significant applications in clinical, industrial and cosmetic sectors. Therefore, researchers have always explored suitable extraction and purification methods for the final application. The different extraction and purification methods of bromelain identified, compared and evaluated. We have also elaborated the pharmaco-kinetics, clinical applications and potential mechanism of action of bromelain. In this research paper, we also focused on different processing methods of bromelain for different purpose of use.